Perbedaan Kemampuan Deteksi Kecurangan Laporan Keuangan antara Auditor Pria dan Wanita Berdasarkan Pengalaman Audit - Lailah Fujianti (Jurnal Riset Akuntansi & Perpajakan (JRAP), 2019)
ABSTRACT The purpose of this study is to investigate the impact of the experience of male auditors and female auditors on their ability to detect fraud, and to further explore the differences in the ability of male and female auditors who are experienced in detecting fraud. The sample of this study was 78 auditors consisting of 47 men and 31 women. Purposive sampling is used to determine the number of research samples. The location of the auditor's office in the DKI Jakarta Region as a consideration in purposive sampling in determining the number of samples. Data analysis method used is Partial Least Square based on variance with multigroub test. The results revealed the experience of male and female auditors had an impact on the ability to detect fraudulent financial statement presentation. Male and female auditors with similar experience are able to detect fraudulent financial statement presentation. The practical implications of this study are expected to be useful as an input in improving the ability of auditors to detect fraud, as well as a basis for policy makers for authorities to consider the need for experience in improving the ability of auditors to detect fraud. The originality of this study is that the ability of experience in improving fraud detection has been studied in many previous studies, but has not classified research samples by gender and has not distinguished the ability of male and female auditors who are experienced in fraud detection. ABSTRAK Tujuan penelitian ini adalah menginvestigasi dampak pengalaman auditor pria serta auditor wanita terhadap kemampuannya dalam deteksi kecurangan, serta mengkaji lebih jauh untuk mengetahui perbedaan kemampuan auditor pria dan wanita yang berpengalaman dalam mendeteksi kecurangan. Sampel penelitian ini adalah 78 auditor yang terdiri dari 47 pria dan 31 wanita. purposive sampling digunakan untuk menentukan jumlah sampel penelitian. Lokasi kantor auditor di Wilayah DKI Jakarta sebagai pertimbangan dalam purposive sampling dalam penetuan jumlah sampel. Metode analisis data yang digunakan adalah Partial Least Square berbasis variance dengan uji multigroub. Hasil penelitian mengungkapkan pengalaman auditor pria serta auditor wanita berdampak terhadap kemampuan deteksi kecurangan penyajian laporan keuangan. Auditor pria maupun wanita yang memiliki pengalaman sama - sama mampu mendeteksi kecurangan penyajian laporan keuangan. Implikasi praktis penelitian ini diharapkan bermanfaat sebagai input dalam meningkatkan kemampuan auditor dalam mendeteksi kecurangan, juga sebagai dasar bagi pengambil kebijakan bagi yang berwenang agar mempertimbangkan perlunya pengalaman dalam meningkatkan kemampuan auditor dalam mendeteksi kecurangan. Adapun originalitas penelitian ini adalah kemampuan pengalaman dalam meningkatkan deteksi kecurangan banyak dikaji pada penelitian terdahulu, akan tetapi belum mengelompokkan sampel penelitian berdasarkan gender dan belum membedakan kemampuan auditor pria dan wanita yang berpengalaman dalam deteksi kecurangan.